Bahasa Arab untuk tujuan Haji dan Umrah / Mohd Sollah Mohamed - Mohd Sollah , Mohamed (2018)
This dissertation is entitled “Arabic Language for Hajj and Umrah Purposes.” The study seeks to explore the needs and effectiveness of a module developed for the purpose of performing Hajj and Umrah. The objectives of the study are to identify the common expressions and vocabulary used when performing Hajj and Umrah as well as in daily routine activities, to explore the specific needs for using the Arabic language when performing Hajj and Umrah, to develop a module and evaluate the suitability and effectiveness of the module. The research adopts a mixed methodology; library research and fieldwork to collect data. The study was carried out in stages; needs analysis of the module, analysis on the development of module and investigation on the effectiveness of the developed module. The researcher utilizes the ADDIE model as the framework for the study. There are five phases in the ADDIE model which are Analysis, Design, Development, Implementation and Evaluation. The preliminary data on analyzing the need to develop the module was obtained via questionnaire distributed to 300 respondents who had performed either Hajj or Umrah in the past. Later, the developed module was investigated for its effectiveness on 30 pilgrims who were performing Umrah in Mecca and Medina during the course of the study. The instruments used in the study were questionnaire, face-to-face interview and observation. The findings show that a majority of the respondents (90%) agreed to use the Arabic language module for the purpose of Hajj and Umrah. On the other hand, the findings on the effectiveness of the module indicate that the effectiveness and suitability of the module achieve a high percentage up to 73%. The result can be based on the circumstances that the module was developed with considerations of the specific needs of the pilgrims of Hajj and Umrah combined with clear,condensed and easily comprehensible presentation of the content in the module. The researcher hopes that the effort puts forth can trigger novel ideas on research related to Arabic language, specifically in the research of Arabic language for specific purposes in Malaysia.